2020
DOI: 10.1007/s00360-020-01321-1
|View full text |Cite
|
Sign up to set email alerts
|

Blood oxygen stores of olive ridley sea turtles, Lepidochelys olivacea are highly variable among individuals during arribada nesting

Abstract: Sea turtles are mostly pelagic, air-breathing divers that can become neritic during nesting season. Sea turtles dive with a full lung of air and these O2 stores are supplemented by O 2 stored in blood. Olive ridley sea turtles exhibit polymorphic nesting behavior; mass nesting behavior called arribada, where up to 25,000 turtles will nest at once, and solitary nesting behavior. As mostly pelagic and highly migratory species, we hypothesize that newly arrived turtles, nesting in arribadas, will exhibit increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 78 publications
(106 reference statements)
1
4
0
Order By: Relevance
“…In a previous study conducted in the same individuals we showed that arribada nesters have higher circulating corticosterone and glucose levels than solitary nesters [32]. Here, we found that arribada nesters are bigger and have higher thyroid hormone levels than solitary nesters.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…In a previous study conducted in the same individuals we showed that arribada nesters have higher circulating corticosterone and glucose levels than solitary nesters [32]. Here, we found that arribada nesters are bigger and have higher thyroid hormone levels than solitary nesters.…”
Section: Discussionsupporting
confidence: 72%
“…While neither TG nor NEFA levels were different between nesting modes (TG: solitary 14.46 ± 9.52 vs arribada 20.47 ± 10.03 mg/mL, t=1.94, p=0.07; NEFA: solitary 0.93 ± 0.22 vs arribada 1.08 ± 0.55 mM, t=0.445, p=0.66), arribada nesters were heavier than solitary nesters (29.20 ± 5.20 vs 24.76 ± 4.37 kg, t=2.17, p=0.042). We then conducted correlation analyses between hormones and metabolites including those (corticosterone, glucose and lactate) measured in samples from the same individuals in a previous study [32]. We found a positive correlation between corticosterone and glucose (ρ=0.87, p<0.0001; Figure 3A ), corticosterone and lactate (ρ=0.73, p=0.005; Figure 3B ), glucose and lactate (r=0.85, p=0.0003; Figure 3C ), and TG and NEFA (r=0.82, p=0.0005; Figure 3D ) in arribada but not in solitary nesters.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…60 No correlation was also found between BM and size and PCV and MHCH in Lepidochelys olivacea from Mexico and only a weak positive relationship with Hb. 6 Although, in hatchlings of Dermochelys coriacea from Florida, there was a significant negative relationship between hatchling BM and WBC and absolute mature Het, and the authors inferred that higher WBC counts and higher mature Het in smaller turtles could be indicative of subclinical active inflammation during development. 43…”
Section: Discussionmentioning
confidence: 98%
“…Similarly, reptiles use a range of physiological mechanisms, including bradycardia, prolonged apnoea, cardiac shunts and Bohr effects, to support diving behaviour (Anderson, 1966; Millard & Johansen, 1974; Seymour & Webster, 1975). In diving turtles, oxygen is stored both in the lungs and blood (Arango et al, 2021; Lutz & Bentley, 1985), and blood oxygen stores are thought to be important in some squamates (Ferguson & Thornton, 1984). Marine snakes have significantly higher haematocrit levels (Brischoux et al, 2011; Feder, 1980), with the file snake Acrochordus granulatus , the species with the largest recorded erythrocytes, having the largest blood oxygen stores of any reptile (Feder, 1980).…”
Section: Discussionmentioning
confidence: 99%